Prevalence and regional disparity of women's autonomy and intimate partner violence in India: evidence from National Family Health Survey-IV 2015-2016, India - Ghosh, Koustav; Mog, Mithun (International Journal Of Community Medicine And Public Health, 2020)
Background: The study was done with the aim to assess the prevalence and regional differences of women autonomy (WA) and Intimate Partner Violence (IPV) in India. Methods: The study utilizes data from the fourth round of National Family and Health Survey, 2015-16, encompassing a sample of 62,716 currently married in the age group of 15-49 years. Bivariate analysis has been performed to draw inferences from the data. Results: Study portrays that 69% of the currently married women live with any autonomy, whereas, 27%, 12% and 7% of them suffer from physical, emotional and sexual violence respectively. The higher level of autonomy has found in North-eastern and Western, whereas, the IPV was found in Eastern and Central parts of India. The major finding from the study was that women from northeast region have better women empowerment and less violence except Manipur against rest region. Conclusion: Women of rural area is still more sufferer of any form of violence and less empowerment existing many major states of India. For better improvement of women empowerment and minimize IPV against women, government need to give more attention to gain progress in every development fields and enhance rural education for rural women particularly.